Conservation agriculture is helping farmers boost their livestock and food security in Zambia - Mhlanga, Blessing; Thierfelder, Christian; Manyawu, Godfrey; Kudzanai Chimhanda (CGIAR, 2024)
Ukama Ustawi Regional Initiative